The effect of a rehabilitative training curriculum to develop some physiological and skill variables in volleyball from sitting for the disabled class F45 - Rasheed , HamadAfat (International Journal of Psychosocial Rehabilitation, 2020)
The activity of volleyball is the disabled sitting category (F45) in a continuous development and development like other sports as it belongs to the group of games in which the performance requires the production of energy to perform fast and strong muscular work, as it was classified within the non-oxygenic games, but the duration of the match was not set at a specific time Makes it necessary to take into account the importance of the antenna system that provides the energy needed by the drunk during the match in order to complete the game, and the importance of the research lies in preparing a training curriculum qualified to develop some physiological and skill variables for the disabled volleyball game (F45) with the aim of developing it in the future to be successful in its representation. The country in the future within the national teams. The research aims to: 1. Developing the vocabulary of a proposed rehabilitative training curriculum to develop some physiological and skill variables in volleyball from sitting for the disabled category (F45). 2. Knowing the effect of the proposed rehabilitation training curriculum on some physiological and skill variables in the game of volleyball from sitting for the disabled (F45). As for the research hypotheses, they are: 1. There are statistically significant differences between the pre and post tests for the experimental and control groups and in favor of the post test in some physiological and skill variables in the game of sitting volleyball for the disabled (F45). 2. There are statistically significant differences in the dimensional tests of the experimental and control groups and in favor of the experimental group in some physiological and skill variables in the volleyball game over sitting for the handicapped group (F45). The researcher used the experimental method on a sample of (20) players from (Al-Wisam and Al Athar) clubs in the Volleyball game for the disabled (F45 class), and (3) physiological tests and two skill tests. In volleyball, the handicapped category (F45) was used, and after processing the data and discussion, the following conclusions were reached: 1. Statistically significant differences between the pre and post test results and in favor of the post test for the experimental and control groups in the results of the physiological tests (the anaerobic step (the anaerobic lactic capacity) and the Harvard step). 2. There were no statistically significant differences between the results of the pre and post tests and the experimental and control group in the test results (vertical stability jump (anaerobic phosphogenic amplitude). 3. There were statistically significant differences between the results of the subsequent tests and in favor of the experimental group in the results of the physiological tests (the anaerobic step (the anaerobic capacity) and the Harvard step), which indicates the effect of the training program prepared by the researcher in developing the physiological variables. 4. There were no statistically significant differences between the meta-tests results between the experimental and control groups in the test results (vertical jump for stability (anaerobic phosphogenic amplitude). 5. There are statistically significant differences between the pre and post test results and in favor of the post test for the experimental and control groups in the results of skill tests B, volleyball from sitting for the handicapped group (F45) in my country. Test my Bermbach’s skills for sending volleyball and receiving transmissions (2). 6. There are statistically significant differences between the results of the subsequent tests and in favor of the experimental group in the results of the skill tests B, Volleyball from Sitting for the Disabled (F45) in my skills Test Brembach for sending the volleyball and receiving the service (2). As for the recommendations, they are: 1. Be guided by the qualifying training approach suggested by volleyball coaches for sitting for the disabled (F45 class). 2. Using the tests that the researcher regularly adopts as an indicator to determine the extent of the development of the physiological and skill variables in volleyball for the disabled (F45) category to see the progress of the players. 3. Conducting studies similar to this study, including other variables not included in the study and other types of disabilities for both sexes.